Keratan sulfate glycosaminoglycan from chicken egg white. (3rd August 2016) - Fu, Li; Sun, Xiaojun; He, Wenqin; Cai, Chao; Onishi, Akihiro; Zhang, Fuming; Linhardt, Robert J; Liu, Zhangguo
Abstract: Keratan sulfate (KS) was isolated from chicken egg white in amounts corresponding to ∼0.06 wt% (dry weight). This KS had a weight-average molecular weight of ∼36–41 kDa with a polydispersity of ∼1.3. The primary repeating unit present in chicken egg white KS was →4) β- N -acetyl-6- O -sulfo-d -glucosamine (1 → 3) β-d -galactose (1→ with some 6- O -sulfo galactose residues present. This KS was somewhat resistant to depolymerization using keratanase 1 but could be depolymerized efficiently through the use of reactive oxygen species generated using copper (II) and hydrogen peroxide. Of particular interest was the presence of substantial amounts of 2, 8- and 2, 9-linked N -acetylneuraminic acid residues in the form of oligosialic acid terminating the non-reducing ends of the KS chains. Most of the KS appears to be N -linked to a protein core as evidenced by its sensitivity to PNGase F.